Self-Efficacy of Padjadjaran University Students in Utilizing Guava Leaf Decoction Water for Diarrhea - Lantang, Rica Nur Aprilia; Setyorini, Dyah; Hernawaty, Taty (Basic and Applied Nursing Research Journal, 2025)
Introduction: Diarrhea remains a global health issue, particularly in vulnerable groups. Guava leaf (Psidium guajava) decoction is widely recognized in traditional medicine for treating diarrhea. Self-efficacy refers to belief in one's ability to apply knowledge in practice, crucial in health contexts. College students were selected as the population due to their potential as future health change agents who can integrate traditional practices into modern healthcare. Objective: This study aimed to assess the self-efficacy of Padjadjaran University students in using guava leaf decoction to manage diarrhea. Method: A descriptive quantitative study with a cross-sectional design was conducted. The sample included 113 students selected through purposive sampling. The General Self-Efficacy Scale (GSES), a standardized tool for measuring belief in one's ability to manage various situations, assessed students' confidence in traditional treatments. Data were collected via Google Forms and analyzed using univariate descriptive statistics. Results: Most students (54.9%) showed low self-efficacy in using guava leaf decoction for diarrhea treatment. Conclusions: The findings highlight the need for educational institutions to strengthen health education by incorporating evidence-based traditional medicine into academic curricula. This can be achieved through complementary nursing courses and awareness initiatives that promote informed, safe use of natural remedies like guava leaf decoction